Missed posterior shoulder dislocation and McLaughlin lesion after an electrocution accident - Rodia Fabio; Ventura Angelo; Touloupakis Georgios; Theodorakis Emmanouil; Ceretti Marco (Chinese Journal of Traumatology, 2012)
【Abstract】Posterior shoulder dislocation is a rare event that may occur after a direct trauma, an epileptic seizure, electric shock or electroconvulsive therapy. In more than 50% of the cases, posterior dislocations are missed on initial evaluation and often misdiagnosed as frozen shoul-ders with unfortunate consequences. We present the case of a missed posterior subluxation and reverse Hill Sachs lesion (McLaughlin lesion) in a 40-year-old woman caused by anelectric shock of 240 V. The patient underwent sur-gery in our institute two weeks after the injury. The humeral head was reduced and the reverse Hill Sachs lesion was filled by demineralized bone matrix allograft with osteoinductive factors. Tendons were repaired and a temporaneous artrodesis was performed. At the final follow up of 12 months, we obtained a Costant Score of 93 and the patient returned to her previous daily activities. Key words: Shoulder dislocation; Electric injuries; Bone matrix